Auditing the representation of hormonal contraceptives in studies assessing exercise performance in women - Flood, T. R.; Clausen, E.; Kuikman, M. A.; Smith, E.; McKay, A. K.; Burke, L. M.; Elliott-Sale, K. J. (Journal of Sports Sciences, 2024)
Hormonal contraceptive (HC) users have a different ovarian hormonal profile compared to eumenorrheic women. Due to the prevalence of HC use amongst sportswomen, there has been increased research efforts to understand their impact on exercise performance. The aim was to audit this research. Studies identified were assessed for HC type, athlete calibre, performance outcome, study design, and quality of methodological control regarding ovarian hormonal profiles. Sixty-eight different HCs were reported across 61 studies. Monophasic combined oral contraceptive (OCP) pills represented 60% of HCs, followed by other pills [34%, phasic-combined, progestogen-only, and un-specified], phasic and long acting reversible contraceptives [5%, vaginal ring, patch, implant, injection, intrauterine system] and unspecified HCs (1%). Eleven percent of participants using HCs were classified as highly trained or elite/international with no participants being classed as world class. Whilst the number of studies involving HCs has increased two-fold over the past decade, the number of studies ranked as gold standard has not increased (HC; 2003-57%, 2011-55%, 2022-43%. OCP; 2003-14%, 2011-17%, 2022-12%). Future research assessing HCs and exercise performance should adopt high-quality research designs and include a broader range of HCs in highly trained to world-class populations to increase the reach and impact of research in this area.